Stuktur Komunitas Fauna Kumbang Sungut Panjang (Coleoptera: Cerambicidae) di Kawasan Taman Nasional Gunung Ciremai - Noerdjito, Woro A. (Perhimpunan Biologi Indonesia, 2008)
ABSTRACTCommunity Structure of Longicorn Beetles Fauna (Coleoptera: Cerambycidae)At Gunung Ciremai National Park. Longicorn beetles (Coleoptera: Cerambycidae)are useful for assessment of recovery of forest insect fauna, because mostly speciesfeed on woody plants and are expected to increase in number and diversity along withdevelopment of the forest. The longicorn beetles were collected at the Gunung CiremaiNational Park (GCNP) area, at Apuy track (Western part of GCNP) during three weeksin April 2006 and Linggarjati track (Eastern part of GCNP) also during three weeks inMay-June 2007. These beetles were collected by Malaise, Light, Artocarpus branchtraps (Bundled twigs of jack fruits tied onto a tree stem) and active collecting by sweeping,beating and handling methods. The specimens collected totally 184 individu, (38 species)which 12 species were noted found at Gunung Halimun Salak National Park (GHSNP)distributed at 1000-1300 meter above sea level.In the research we found Acalolepta rusticatrix, Epepeotes luscus and Pterolophiamelanura that known as a common species of Cerambycid or longhorn beetles inKalimantan and Java, were found in the research activities, caused these species foundat many places including at Bogor Botanical Garden. In GCNP, we did not find Nyctimeniusochraceovittata as indicator for relatively less disturbed forest in Kalimantan, otherwisewe find Nyctimenius varicornis mostly find in all study site at GCNP, that is possible asindicator for relatively less disturbed forest in Java. In GCNP, we find Gnoma longicollisas a cerambycid beetle for natural forest indicator. In the paper show the comparativediversity study between traps (collecting methods) and study site (habitat and altitude).Key word: Cerambycidae, Ciremai, struktur komunitas